2013
DOI: 10.4161/viru.24886
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating gene expression (AGE) for vaccine development

Abstract: Live attenuated vaccines are adept in stimulating protective immunity. Methods for generating such vaccines have largely adopted strategies used with Salmonella enterica. Yet, when similar strategies were tested in other gram-negative bacteria, the virulence factors or genes responsible to incapacitate Salmonella often failed in providing the desired outcome. Consequently, conventional live vaccines rely on prior knowledge of the pathogen’s virulence factors to successfully attenuate them. This can be problema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Alternatively, anachronistic overexpression of the batA gene product may attenuate B. mallei. This phenomenon has been reported in the literature as a platform to develop live attenuated vaccines, termed attenuated gene expression (127). The molecular basis of attenuation is not fully understood and varies between model systems.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, anachronistic overexpression of the batA gene product may attenuate B. mallei. This phenomenon has been reported in the literature as a platform to develop live attenuated vaccines, termed attenuated gene expression (127). The molecular basis of attenuation is not fully understood and varies between model systems.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization with Salmonella vaccines synthesizing F1 antigen induced protective immunity against plague [39-43]. However, the virulence of S. typhimurium P1 containing a caf1 expression plasmid was dramatically reduced due to its growth retardation and the disruption of its membrane caused by F1 overexpression [44, 45]. Our observations also showed that the F1 overexpression in Yptb PB1+ strain containing a caf1 expression plasmid severely affected its growth, could not colonize in spleens and livers of mice and barely induced protective immunity against plague (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…[65, 66] Interestingly, instead of deleting genes, some investigators have attenuated bacteria by overexpressing bacterial surface appendages such as flagella and pili using a method termed Attenuated Gene Expression (AGE). [67]…”
Section: Methods Of Attenuationmentioning
confidence: 99%